Effect of plant nutrient and weed management in direct wet seeded boro rice - Sarkar, MAR; Paul, SK; Paul, U (Progressive Agriculture, 2017)
The experiment was conducted at the Farm of Farm Management Division, Bangladesh Agricultural University, Mymensingh during December 2012 to June 2013 to find out the effect of plant nutrient and weed management in direct wet seeded Boro rice. The experiment consisted of six nutrient management viz. Control (No manure- PM and N-P-K-S-Zn), PM at 5 t ha-1, recommended dose of prilled urea (PU) and other inorganic fertilizers (i. e. 120, 60, 40, 10 and 5 kg of N, P2O5, K2O, S and ZnSO4, respectively), full dose of Urea Super Granules (USG) and other inorganic fertilizers (i. e. 60, 40, 10 and 5 kg of P2O5, K2O, S and ZnSO4, respectively) 2.7 g USG + PM at 5 t ha-1, 2.7 g USG + PM at 2.5 t ha-1; and three weeding regimes, viz. Unweeded control, hand weeding thrice at 20, 35 and 50 days after sowing (DAS); and Panida (Pandimethalin) @ 2.5 l ha-1 and hand weeding once at 20 DAS. The highest plant height (90.29 cm) was obtained in full dose of USG and other inorganic fertilizers (i. e. 60, 40, 10 and 5 kg of P2O5, K2O, S and ZnSO4 respectively) and the lowest one (82.42 cm) was from control (No manure- PM and N-P-K-S-Zn). The highest number of effective tillers hill-1 (14.00) was obtained in recommended dose of PU and other inorganic fertilizers (i. e. 120, 60, 40, 10 and 5 kg of N2, P2O5, K2O, S and ZnSO4 respectively) whereas the lowest effective tillers hill-1 9.15 was obtained from control (No manure- PM and N-P-K-S-Zn). The highest number of grains panicle-1 (75.23) was observed in nutrient 2.7 g USG + PM at 5 t ha-1 and the lowest one (59.01) was obtained from PM at 5 t ha-1.The highest plant height (90.57 cm) was obtained in Panida (Pandimethalin) @ 2.5 l ha-1 and hand weeding once at 20 DAS and lowest plant height (83.98 cm) was obtained in un weeded control. The maximum grain yield (3.71 t ha-1) was obtained from the application of 2.7 g USG + PM at 2.5 t ha-1 and the lowest (1.15 t ha-1) was from control (No manure- PM and N-P-K-S-Zn). The highest grain yield (3.8 t ha-1) was obtained in Panida (Pandimethalin) @ 2.5 l ha-1 and hand weeding once at 20 DAS and the lowest one (1.26 t ha-1) was obtained from unweded control. In case of interaction, the highest number of effective tillers hill-1 (17.00) was obtained in recommended dose of PU and other inorganic fertilizers (i.e. 120, 60, 40, 10 and 5 kg of N, P2O5, K2O, S and ZnSO4 respectively) with hand weeding thrice at 20, 35 and 50 DAS and the lowest one (7.27) was observed in control (No manure- PM and N-P-K-S-Zn) with no weeding. The highest grain yield (5.29 t ha-1) was obtained in 2.7 g USG + PM at 2.5 t ha-1 with Panida (Pandimethalin) @ 2.5 l ha-1 and hand weeding once at 20 DAS which was statistically identical with 2.7 g USG + PM at 5 t ha-1 and Panida (Pandimethalin) @ 2.5 l ha-1 and hand weeding once at 20 DAS and the lowest grain yield (0.65 t ha-1) was obtained in the interaction of unweeded and unfertilized control (No manure- PM and N-P-K-S-Zn). Boro rice (cv. BRRI dhan28) can be cultivated with 2.7 g USG applied at the centre of the four hills in each alternate row + PM at 2.5 t ha-1 with Panida (Pandimethalin) @ 2.5 l ha-1 and hand weeding once at 20 DAS for appreciable grain yield. Progressive Agriculture 27 (4): 466-472, 2016